2022
DOI: 10.3390/ma15103532
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Material-Characterization Properties of Post-Production Waste—The Case of Apple Pomace

Abstract: The paper presents the material-characterization properties of apple pomace—the post-production waste of juice pressing. Tests were carried out on the basic physical properties of apple pomace: color, specific-density, and energy properties. Extensive material-composition analyses based on DSC (differential scanning calorimetry) and TGA (thermogravimetry) methods were also performed. It has been shown that pomace, due to its energy value, can be a good fuel. The obtained thermal data confirm the presence of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…This view was echoed in the interview findings, with the primary producers in this study finding alternative ways of using the produce that is not accepted by their customers, such as for fertilizing the land or feeding their animals. Research has also shown that waste materials from primary processing have further potential as new energy sources [51]. Like this study, studies from Richards et al [52] and Messner et al [10] focusing on Australian horticulture found that there were many "paradoxes" connected with the generation of food surplus in primary production, with a blame game happening in terms of who is responsible for the surplus, but ultimately feeling powerless to create change with the buyers, which are often the retailers in control.…”
Section: Types Of Surplus Materials Availablementioning
confidence: 99%
“…This view was echoed in the interview findings, with the primary producers in this study finding alternative ways of using the produce that is not accepted by their customers, such as for fertilizing the land or feeding their animals. Research has also shown that waste materials from primary processing have further potential as new energy sources [51]. Like this study, studies from Richards et al [52] and Messner et al [10] focusing on Australian horticulture found that there were many "paradoxes" connected with the generation of food surplus in primary production, with a blame game happening in terms of who is responsible for the surplus, but ultimately feeling powerless to create change with the buyers, which are often the retailers in control.…”
Section: Types Of Surplus Materials Availablementioning
confidence: 99%